Entropy and the Tao of Counting : A Brief Introduction to Statistical Mechanics and the Second Law of Thermodynamics /: A Brief Introduction to Statistical Mechanics and the Second Law of Thermodynamics. ([2019]) - Sharp, Kim
No abstract available